Dimeric Pimprinine Alkaloids From Soil-Derived Streptomyces sp. NEAU-C99 - Yu, Zhiyin; Jiang, Hao; Wang, Li; Yang, Feng-Xian; Huang, Jian-Ping; Liu, Chongxi; Guo, Xiaowei; Xiang, Wensheng; Huang, Sheng-Xiong (Frontiers in Chemistry, 2020)
Six new pimprinine alkaloids (1–6), including four dimers, dipimprinines A−D (1−4), and two monomers, (±)-Pimprinol D (5) and pimprinone A (6), along with six known congeners (7–12), were isolated from a soil-derived actinomycete Streptomyces sp. NEAU C99. Structures of the new compounds were elucidated by extensive spectroscopic analyses, single-crystal X-ray diffractions, and ECD calculations. Dipimprinines A−D (1−4) showed weak cytotoxic activities against five tumor cell lines, including HL-60, SMMC-7721, A-549, MCF-7 and SW-480, with IC50 values ranging from 12.7 μM to 30.7μM.